DAMPAK EDUKASI VIDEO DAN LEAFLET TERHADAP PENGETAHUAN ORANG TUA TENTANG ISPA - Bawinto, Janike Arista; Sepang, Mareyke Yolanda Lusia; Langelo, Wahyuny (Lasalle Health Journal, 2024)
Introduction: Acute Respiratory Infections (ARI) are a significant public health problem, especially in children. This disease can cause various serious complications and even death. One of the factors that influences the handling of ISPA is the level of knowledge of parents. Providing health education using video media and leaflets is important. Objective: This research aims to determine the effect of providing education using video media and leaflets on parents' level of knowledge about the incidence of ISPA in children. Method: The research uses a quantitative design with a pre-experimental research design using one group pre-test and post-test. The population in this study were all parents who had children aged 5 years and under as many as 54 people with data collection techniques using purposive sampling with a sample size of n = 30 respondents. This research uses the Wilcoxon test. Results: the video and leaflet method was effective on parents' level of knowledge about ISPA. Conclusion: There is a difference in the level of knowledge of parents before and after health education using video media and leaflets about events.